Combination chemotherapy using core-shell nanoparticles through the self-assembly of HPMA-based copolymers and degradable polyester - Jäger, Eliézer; Jäger, Alessandro; Chytil, Petr; Etrych, Tomáš; Ríhová, Blanka; Giacomelli, Fernando Carlos; Stěpánek, Petr; Ulbrich, Karel (Journal of controlled release, 2013)
The preparation of core-shell polymeric nanoparticles simultaneously loaded with docetaxel (DTXL) and doxorubicin (DOX) is reported herein. The self-assembly of the aliphatic biodegradable copolyester PBS/PBDL (poly(butylene succinate-co-butylene dilinoleate)) and HPMA-based copolymers (N-(2-hydroxypropyl)methacrylamide-based copolymers) hydrophobically modified by the incorporation of cholesterol led to the formation of narrow-size-distributed (PDI<0.10) sub-200-nm polymeric nanoparticles suitable for passive tumor-targeting drug delivery based on the size-dependent EPR (enhanced permeability and retention) effect. The PHPMA provided to the self-assembled nanoparticle stability against aggregation as evaluated in vitro. The highly hydrophobic drug docetaxel (DTXL) was physically entrapped within the PBS/PBDL copolyester core and the hydrophilic drug doxorubicin hydrochloride (DOX·HCl) was chemically conjugated to the reactive PHPMA copolymer shell via hydrazone bonding that allowed its pH-sensitive release. This strategy enabled the combination chemotherapy by the simultaneous DOX and DTXL drug delivery. The structure of the nanoparticles was characterized in detail using static (SLS), dynamic (DLS) and electrophoretic (ELS) light scattering besides transmission electron microscopy (TEM). The use of nanoparticles simultaneously loaded with DTXL and DOX provided a more efficient suppression of tumor-cell growth in mice bearing EL-4 T cell lymphoma when compared to the effect of nanoparticles loaded with either DTXL or DOX separately. Additionally, the obtained self-assembled nanoparticles enable further development of targeting strategies based on the use of multiple ligands attached to an HPMA copolymer on the particle surface for simultaneous passive and active targeting and different combination therapies.
Keywords: Doxorubicin; Models, Molecular; taxoidy; Lymphoma, T-Cell; methakryláty; Nanoparticles; Docetaxel; myši inbrední C57BL; Taxoids; Methacrylates; Mice; polyestery; lékové transportní systémy; Antineoplastic Agents; docetaxel; doxorubicin; molekulární modely; protinádorové látky; zvířata; nanočástice; Polyesters; myši; lymfom T-buněčný; Drug Delivery Systems; Mice, Inbred C57BL; Animals